Leverage on small-scale primordial non-Gaussianity through cross-correlations between CMB E-mode and μ-distortion anisotropies. Issue 1 (24th February 2022) - Remazeilles, Mathieu; Ravenni, Andrea; Chluba, Jens
ABSTRACT: Multifield inflation models and non-Bunch–Davies vacuum initial conditions both predict sizeable non-Gaussian primordial perturbations and anisotropic μ-type spectral distortions of the cosmic microwave background (CMB) blackbody. While CMB anisotropies allow us to probe non-Gaussianity at wavenumbers $k\simeq 0.05\, {\rm Mpc^{-1}}$, μ-distortion anisotropies are related to non-Gaussianity of primordial perturbation modes with much larger wavenumbers, $k\simeq 740\, {\rm Mpc^{-1}}$ . Through cross-correlations between CMB and μ-distortion anisotropies, one can therefore shed light on the aforementioned inflation models. We investigate the ability of a future CMB satellite imager like LiteBIRD to measure μ T and μ E cross-power spectra between anisotropic μ-distortions and CMB temperature and E -mode polarization anisotropies in the presence of foregrounds, and derive LiteBIRD forecasts on ${f_{\rm NL}^μ (k\simeq 740\, {\rm Mpc^{-1}})}$ . We show that μ E cross-correlations with CMB polarization provide more constraining power on $f_{\rm NL}^μ$ than μ T cross-correlations in the presence of foregrounds, and the joint combination of μ T and μ E observables adds further leverage to the detection of small-scale primordial non-Gaussianity. For multifield inflation, we find that LiteBIRD would detect ${f_{\rm NL}^μ }=4500$ at 5σ significance after foreground removal, and achieve a minimum error of ${σ (f_{\rm NL}^μ =0) \simeq 800}$ at 68 per cent CL by combining CMB temperature and polarization. Due to the huge dynamic range of wavenumbers between CMB and μ-distortion anisotropies, such large $f^μ _{\rm NL}$ values would still be consistent with current CMB constraints in the case of very mild scale dependence of primordial non-Gaussianity. Anisotropic spectral distortions thus provide a new path, complementary to CMB B -modes, to probe inflation with LiteBIRD .